Serum CCL20 combined with IL-17A as early diagnostic and prognostic biomarkers for human colorectal cancer - Wang, Dan; Yuan, Weitang; Wang, Yaping; Wu, Qian; Yang, Li; Li, Feng; Chen, Xinfeng; Zhang, Zhen; Yu, Weina; Maimela, Nomathamsanqa Resegofetse; Cao, Ling; Wang, Dong; et al. (Journal of translational medicine, 2019)
Noninvasive and effective methods of early diagnosis of colorectal cancer (CRC) are underexplored. Inflammation is known to play an important role in the tumor microenvironment of CRC. Therefore, the aim of this study was to elucidate novel inflammatory biomarkers related to early diagnosis and prognosis of CRC. Based on the results from a multiplex assay and a pan-cancer screening of TCGA data with 18 cancer types, we identified several targeted biomarkers. We further confirmed these results using a trial cohort of 112 CRC patients and 151 controls (59 healthy donors, 52 colitis and 40 colorectal adenoma patients) by Elisa and immunohistochemistry (IHC). The biomarkers expression levels in CRC patients of different clinical stages were compared. The targeted biomarkers panel was developed using logistic regression model and was then validated using an independent cohort including 75 CRC patients and 90 controls (35 healthy donors, 20 colitis and 35 colorectal adenoma patients). Diagnostic accuracy was evaluated using area under the receiver-operating characteristic (ROC) curve and overall survival analysis was used for prognosis. Gene ontology (GO) analyses and Gene set enrichment analyses (GSEA) were performed to predict the function of the candidate biomarkers. CCL20 and IL-17A were identified as candidate biomarkers using multiplex assay and pan-cancer screening of TCGA data. Elisa and IHC demonstrated that both CCL20 and IL-17A levels were highly expressed in CRC patients, more especially in patients with advanced stage disease. A signature expression of the two biomarkers showed high diagnostic accuracy of CRC. Importantly, the diagnostic sensitivity and specificity were still satisfactory in the early stage and low carcinoembryonic antigen (CEA) level groups. Bioinformatics analysis revealed that CCL20 and IL-17A may be involved in CRC progression. In addition, the diagnostic performance of CCL20 and IL-17A in combination was superior to that of either marker alone. Serum CCL20 and IL-17A levels were identified as independent prognostic markers for CRC. The CCL20-IL-17A panel exhibited a good performance in the diagnosis of early stage CRC.